PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP DISIPLIN KERJA SERTA IMPLIKASINYA PADA KINERJA PEGAWAI SEKRETARIAT DPRD OGAN ILIR - Rustam Effendi; Amrillah Azrin (Fakultas Ekonomi Universitas Tridinanti Palembang, 2019)
ABSTRACTThis study aims to determine the Effect of Leadership and Motivation on Work Discipline and Its Implications on the Performance of Ogan Ilir DPRD Secretariat Staff. Considering the population is only 50 people, the entire population is used as the research sample, which means that the sampling uses saturated sampling. Based on data analysis carried out with the Partial Least Square (PLS) method, the following results were obtained: First hypothesis: leadership (X1) had a positive and significant effect on work discipline (Z). the result of t-Statistic value is 5.008 96 1.96, so it is concluded that there is a significant influence of leadership on work discipline. The second hypothesis: motivation (X2) has a positive and significant effect on work discipline (Z). the result of the t-statistic value is 6.760 96 1.96, so it is concluded that there is a significant effect of work discipline on work discipline. The third hypothesis: leadership (X1) has a positive and significant effect on performance (Y). the results of the T-Statistics value are 8.554 96 1.96, so it is concluded that there is a significant influence of leadership on performance. The fourth hypothesis: motivation (X2) has a positive and significant effect on performance (Y). the results of the T-Statistics value are 4.265 ≥ 1.96, so it is concluded that there is a significant effect of motivation on performance. The fifth hypothesis: work discipline (Z) has a positive and significant effect on performance (Y). the result of the T-statistic value is 2.576 96 1.96, so it is concluded that there is a significant effect of work discipline on performance. Leadership towards the performance of the Ogan Ilir DPRD Secretariat Staff has an indirect influence on work discipline as a mediating variable or an intermediary variable proven by looking at the table above with a T-statistic value of 2.476 ≥ 1.96. Motivation on the performance of the Secretariat Staff of the Ogan Ilir DPRD has an indirect influence with the work discipline as a mediating variable or an intermediary variable proven by looking at the table above with a T-statistic value of 7.907 96 1.96. From the analysis obtained can be seen the magnitude of the effect produced by exogenous variables on endogenous variables can see the value of R2 for latent variable work discipline as a mediating variable of 0.998, which means that the value identifies that variations in work discipline can be explained by exogenous latent variables (leadership and motivation ) amounting to 99.8% while the remaining 0.2% is explained by other variables and the R2 value for the performance latent variable is 0.995, which means that the value identifies that variations in performance can be explained by exogenous variables of 99.5% while the remainder is 0, 5% is explained by variables not found in the study. Keywords: Performance, Leadership, Motivation and Work Discipline